2007
DOI: 10.1053/j.gastro.2007.05.014
|View full text |Cite
|
Sign up to set email alerts
|

How Does Cognitive Behavior Therapy for Irritable Bowel Syndrome Work? A Mediational Analysis of a Randomized Clinical Trial

Abstract: Background & Aims: While multiple clinical trials support the efficacy of psychological treatments for reducing IBS symptoms, the mechanisms responsible for symptomatic improvement are unknown. One hypothesis is that psychological treatments work by alleviating comorbid psychological distress implicated in the worsening of bowel symptoms and quality of life. An alternative hypothesis assumes that changes in distress are not strictly a cause but a consequence of IBS that will decrease with symptomatic improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
3
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 51 publications
3
142
3
4
Order By: Relevance
“…There is no evidence that patients' attributions for their illness and expectations/preferences for intervention influence the efficacy in any treatment. It is suggested that some patients do not understand the cognitive behavior model as applying to them and are thus unlikely to engage in CBT [61] . As this is a therapy which makes significant demands on patients' time, some Lynch et al [52] Canada 21 CBT Heymann-Monnikes et al [53] Germany 20 CBT Sanders et al [54] United States 28 CBT Hunt et al [55] United States 54 CBT Moss-Morris et al [56] England 64 CBT Craske et al [40] United States 110 CBT Ljotsson et al [57] Sweden 195 CBT Ljotsson et al [58] Sweden 61 CBT Oerlemans et al [59] The Netherlands 75 CBT CBT: Cognitive-behavioral therapy.…”
Section: Potential Problemsmentioning
confidence: 99%
“…There is no evidence that patients' attributions for their illness and expectations/preferences for intervention influence the efficacy in any treatment. It is suggested that some patients do not understand the cognitive behavior model as applying to them and are thus unlikely to engage in CBT [61] . As this is a therapy which makes significant demands on patients' time, some Lynch et al [52] Canada 21 CBT Heymann-Monnikes et al [53] Germany 20 CBT Sanders et al [54] United States 28 CBT Hunt et al [55] United States 54 CBT Moss-Morris et al [56] England 64 CBT Craske et al [40] United States 110 CBT Ljotsson et al [57] Sweden 195 CBT Ljotsson et al [58] Sweden 61 CBT Oerlemans et al [59] The Netherlands 75 CBT CBT: Cognitive-behavioral therapy.…”
Section: Potential Problemsmentioning
confidence: 99%
“…CBT has been found to be effective in hospital patients with IBS, however recent trials have reported equivocal results 55,56 . A number of clinical trials support the efficacy of CBT when administered over multiple (weekly) sessions by trained therapists in tertiary care settings 57,58 -the outcomes include improvement in key gastrointestinal symptoms (pain, bowel dysfunction), quality of life 59 , and psychological distress 60 . CBT has practical limitations (high cost, shortage of adequately trained therapists, long waiting lists, time requirements) that hamper its clinical utility.…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%
“…With regard to the CBT mechanism in IBS, several studies suggest that the change may occur through: (1) improvement in psychological distress which leads to improvement in GI symptoms [26]; (2) direct effect of CBT on GI symptoms that in turn may lead to reductions in psychological distress [28,29]; (3) changes first of the behaviour, then of the cognition, before impacting on treatment outcome [28,30]; decrease of visceral sensitivity and of catastrophic cognitions [31]. An interesting aspect mentioned by the authors of a 2015 metaanalysis [32] is that psychological treatments for IBS, which have the same treatment labels (e.g.…”
Section: How Do Cbt and Gut-directed Hypnosis Work?mentioning
confidence: 99%
“…on bowel symptoms) [26,29], (3) analyse if the specific skill used in treatment improves after treatment (e.g. mindfulness) [38], (4) make attempts to measure intermediate constructs at baseline and post-treatment, and (5) try to examine the mediation of symptom improvements through these intermediate constructs quantitatively [39].…”
Section: How Do Cbt and Gut-directed Hypnosis Work?mentioning
confidence: 99%
See 1 more Smart Citation